2003
DOI: 10.1152/ajpendo.00540.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of NF-κB and AP-1 in increased fibronectin synthesis in target organs of diabetic complications

Abstract: Increased extracellular matrix protein production leading to structural abnormalities is a characteristic feature of chronic diabetic complications. We previously showed that high glucose in endothelial cell culture leads to the upregulation of basement membrane protein fibronectin (FN) via an endothelin (ET)-dependent pathway involving activation of NF-κB and activating protein-1 (AP-1). To delineate the mechanisms of basement membrane thickening, we used an animal model of chronic diabetes and evaluated ET-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 41 publications
14
157
0
1
Order By: Relevance
“…[1][2][3][4][5]18 We have previously demonstrated an important role of hyperglycemia-induced ET-1 expression in increased ECM protein deposition. 4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats. 4,15 Bosentan treatment also prevented retinal capillary and glomerular basement membrane thickening in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5]18 We have previously demonstrated an important role of hyperglycemia-induced ET-1 expression in increased ECM protein deposition. 4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats. 4,15 Bosentan treatment also prevented retinal capillary and glomerular basement membrane thickening in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that both NF-kB and AP-1 may be of importance in this scenario. 6,18 EMSA showed glucose-induced activation of both NF-kB and AP-1 in endothelial cells ( Figure 7). Inhibition of MAPK pathway caused marked attenuation of both NF-kB and AP-1 activation (Figure 7).…”
Section: Transcription Factor Involvement In Mapk-mediated Signaling mentioning
confidence: 98%
See 1 more Smart Citation
“…Total RNA was extracted using Trizol (Invitrogen), the samples were centrifuged (12,000g ϫ 15 min), and RNA was isolated from the aqueous layer and precipitated using isopropyl alcohol. RNA (3 g) was used for cDNA synthesis according to the methods described previously (30). Briefly, RNA was mixed with oligo-d(T) primers and incubated for 10 min at 70°C.…”
Section: Methodsmentioning
confidence: 99%
“…Once activated, NF‐κB, additionally drives the expression of numerous growth factors, such as connective tissue growth factor (CTGF) and TGF‐β 113. This, in turn, drives the production of extracellular matrix (ECM) proteins in the heart, including collagen, fibronectin and proteoglycans, leading to fibrosis, LV remodelling and stiffness, and reduced relaxation of the heart 108, 117. Moreover, a clinical study showed a correlation between macrophage inhibitory factor and the development of diastolic dysfunction in diabetic patients 116.…”
Section: Diabetic Cardiomyopathy Antioxidant Defences and Immunothermentioning
confidence: 99%